Casos y cosas: semanario popular (Vol. 1, No. 42) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Las infamias de un cobarde, Y agradeció a sus amigos?, Electores en aeroplano, Lo que yó he visto...., Mis últimas lamentaciones, ¿Cuántas costillas tienen las mujeres?, Amores misteriosos…

ENGLISH: The infamies of a coward, and thanked his friends?, Electors in an airplane, what I have seen...., My last lamentations, How many ribs do women have, Mysterious loves?
Cases and things: popular weekly (Vol. 1, No. 42)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas